Przekaz Al-Dżahiza o wierzeniach Słowian. Folklorystyka w badaniach nad prasłowiańską mitologią - Kowalski, Andrzej Piotr; Rychło, Mikołaj; Witczak, Krzysztof Tomasz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
The paper concentrates on the Slavic snake myth; it includes creatures believed to suckle milk from cattle udders. We argue that this myth (so far mainly associated with folklore) reflects very ancient beliefs held by our ancestors and can be independently confirmed in several sources. Most noteworthy among them is a ninth century note included by al-Jāḥiẓ in his Kitāb al-ḥayawān (Book of Animals) which we quote in the paper. The Arab writer reports in detail on the behaviour of cow-suckling snakes which he knew from his personal interaction with Slavs. Further evidence comes from comparative data which we adduce from our source material. These include, among others, motifs referring to snakes and cows from the Rigveda. There are also historical sources, such as a description of a cow-milking snake by Jakub Kazimierz Haur (1693), and etymological arguments. We conclude that since it is sometimes possible to find independent confirmation of what is reconstructed (as in the case of the Proto-Slavic beliefs about milk-sucking snakes), we should be less sceptical about the products of comparative methods and their value.